Spanish Economic Growth, 1850-2015 - Leandro Prados de la Escosura (Palgrave Studies in Economic History, 2017)
This text offers a comprehensive and nuanced view of the economic development of Spain since 1850. It provides a new set of historical GDP estimates for Spain from the demand and supply sides, and presents a reconstruction of production and expenditure series for the century prior to the introduction of modern national accounts. The author splices available national accounts sets over the period 1958-2015 through interpolation, as an alternative to conventional retropolation. The resulting national accounts series are linked to the historical estimates providing yearly series for GDP and its components since 1850. On the basis of new population estimates, the author derives GDP per head, decomposed into labour productivity and the amount of work per person, and placed into international perspective. With theoretical reasoning and historiographical implications, Prados de la Escosura provides a useful methodological reference work for anyone interested in national accounting.